Sedation Usage in COVID-19 Acute Respiratory Distress Syndrome: A Multicenter Study. Issue 2 (February 2022) - Tapaskar, Natalie; Colon Hidalgo, Daniel; Koo, Grace; Shingada, Krupa; Rao, Swathi; Rodriguez, Raul; Alcantar, Daniel; Espinoza Barrera, Diana; Lee, Raymond; Rameshkumar, Naveen; Amine, Mukarram; Rodrigues, Shelden; et al.
Background: Patients with COVID-19 acute respiratory distress syndrome (ARDS) have been shown to have high sedation requirements. Objective: The purpose of this study was to compare sedative use between patients with COVID-19 ARDS and non-COVID-19 ARDS. Methods: This was a retrospective study of patients with COVID-19 ARDS compared with historical controls of non-COVID-19 ARDS who were admitted to 2 hospitals from March 1, 2020, to April 30, 2020, and April 1, 2018, to December 31, 2019, respectively. The primary outcome was median cumulative dose of propofol (µg/kg) at 24 hours after intubation. Results: There were 92 patients with COVID-19 ARDS and 37 patients with non-COVID-19 ARDS included. Within the first 24 hours of intubation, patients with COVID-19 ARDS required higher total median doses of propofol: 51 045 µg/kg (interquartile range, 26 150-62 365 µg/kg) versus 33 350 µg/kg (9632-51 455 µg/kg; P = 0.004). COVID-19 patients were more likely receive intravenous lorazepam (37% vs 14%; P = 0.02) and higher cumulative median doses of midazolam by days 5 (14 vs 4 mg; P = 0.04) and 7 of intubation (89 vs 4 mg; P = 0.03) to achieve the same median Richmond Analgesia-Sedation Scale scores. COVID-19 ARDS patients required more ventilator days (10 vs 6 days; P = 0.02). There was no difference in 30-day mortality. Conclusion and Relevance: Patients with COVID-19 ARDS required higher doses of propofol and benzodiazepines than patients with non-COVID-19 ARDS to achieve the same median levels of sedation.